Major pathogenic steps in human lupus can be effectively suppressed by nucleosomal histone peptide epitope-induced regulatory immunity - Zhang, Li; Bertucci, Anne M.; Ramsey-Goldman, Rosalind; Harsha-Strong, Elizabeth Randall; Burt, Richard K.; Datta, Syamal K. (Clinical immunology (Orlando, Fla.), 2013)
Low-dose tolerance therapy with nucleosomal histone peptide epitopes blocks lupus disease in mouse models, but effect in humans is unknown. Herein, we found that CD4+CD25highFoxP3+ or CD4+CD45RA+FoxP3low T-cells, and CD8+CD25+FoxP3+ T-cells were all induced durably in PBMCs from inactive lupus patients and healthy subjects by the histone peptide/s themselves, but in active lupus, dexamethasone or hydroxychloroquine unmasked Treg-induction by the peptides. The peptide-induced Treg depended on TGFβ/ALK-5/pSmad 2/3 signaling, and they expressed TGF-β precursor LAP. Lupus patients' sera did not inhibit Treg induction. The peptide epitope-induced T cells markedly suppressed type I IFN related gene expression in lupus PBMC. Finally, the peptide epitopes suppressed pathogenic autoantibody production by PBMC from active lupus patients to baseline levels by additional mechanisms besides Treg induction, and as potently as anti-IL6 antibody. Thus, low-dose histone peptide epitopes block pathogenic autoimmune response in human lupus by multiple mechanisms to restore a stable immunoregulatory state. •Immunoregulatory effects of nucleosomal histone peptide epitopes in humans revealed•Histone peptide epitopes induce Treg cells in healthy humans and lupus patients.•Peptide epitope-induced human Treg are TGFβ−dependent and express TGFβ-LAP.•Peptides inhibit autoantibody production in human lupus by additional mechanisms.•Peptide-induced Treg suppress type I interferon gene expression in human lupus.